Requirements for some Marine Fish Species with an Emphasis on Organic Ingredients - Cuzon, G.; Maldonado, C.; Gaxiola, G. (Facultad de Ciencias Biologicas, 2013)
Actually some fish are well known as for their nutritional requirements such as salmon, red drum, grouper. There is consistent information on protein, lipid and sometimes energy. However, energy is under evaluated for species except salmonids. Some information is lacking on digestible energy for main ingredients, as well as for energy density of fish for some new candidate species such as Platax orbicularis, Centropomus undecimalis. Moreover, there is sometimes a discrepancy between the actual data on requirement and what is proposed in commercial feeds. Some company proposed a unique feed for marine specials (all in one) and some farmers select feeds not so in line with the real need of their species; lack of performances or lack of profitability of the production system. In terms of innovation the concept “organic” become more and more in favor for many producers or coordinating bodies to develop fish farming.